How to Thrive at Work Mindfulness, Motivation and Productivity. - Mordue, Stephen J. (Business in Mind., 2021)
Tried and tested strategies to promote mindfulness, motivation and productivity at work, this book helps you face the demands of your job whatever your working environment and whatever stage you are at in your career.